2005
DOI: 10.1210/jc.2004-1364
|View full text |Cite
|
Sign up to set email alerts
|

Serum Adiponectin and Resistin Concentrations in Patients with Restrictive and Binge/Purge Form of Anorexia Nervosa and Bulimia Nervosa

Abstract: To study the role of adipose tissue-derived hormones in the pathophysiology of eating disorders, circulating levels of adiponectin, resistin, and other hormonal and metabolic parameters were measured in 16 females with the restrictive subtype of anorexia nervosa (R-AN), 10 females with the binge/purge subtype of anorexia nervosa (P-AN), 15 females with bulimia nervosa (BN), and 12 age-matched healthy females (C). Body mass index (BMI), body fat content, and serum leptin levels were severely decreased in R-AN a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
63
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(72 citation statements)
references
References 29 publications
7
63
2
Order By: Relevance
“…The subgroup of BP-AN patients showed significantly higher adiponectin levels compared with R-AN patients. These results are not in agreement with the study of Housova et al (2005), which did not observe any difference between R-AN and BP-AN forms. Other studies showed an increase in serum adiponectin levels in AN but did not deal with AN subtypes Pannacciulli et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The subgroup of BP-AN patients showed significantly higher adiponectin levels compared with R-AN patients. These results are not in agreement with the study of Housova et al (2005), which did not observe any difference between R-AN and BP-AN forms. Other studies showed an increase in serum adiponectin levels in AN but did not deal with AN subtypes Pannacciulli et al, 2003).…”
Section: Discussioncontrasting
confidence: 99%
“…Although the serum leptin levels of the H-AN patients are low compared with the control subjects, the relative increase of these hormone levels in this H-AN group compared with the NH-AN patients could contribute to the worse outcome observed in H-AN patients. This is the first study showing a decrease of serum resistin levels in H-AN patients compared with NH-AN patients, despite the fact that we found no difference in serum resistin values in the whole AN group compared with healthy control women, as seen in other studies (Housova et al, 2005). The H-AN patients tend to be more insulin sensitive than the NH-AN patients.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…In particular, many studies demonstrated elevated adiponectin serum levels in female patients affected with anorexia nervosa (ModanMoses et al 2007;Pannacciulli et al 2003;Terra et al 2013), while binge eating disorder was related to decreased circulating adiponectin (Monteleone et al 2003;Carnier et al 2012). It is worth noting that inconsistent data exist for patients suffering from bulimia nervosa (Housova et al 2005;Tagami et al 2004;Monteleone et al 2003). Taken together, besides its well-known effects in terms of obesity, type 2 diabetes and related metabolic conditions adiponectin seems to be involved in food intake and energy expenditure as well as in the pathophysiology of eating disorders.…”
Section: Introductionmentioning
confidence: 99%
“…Although leptin and adiponectin in the adipocytokine signaling pathway are related to anorexia nervosa and bulimia nervosa [45,46], other downstream signaling circuits have not been reported to be related to eating disorder. Based on our gene collection, most of the genes in the adipocytokine signaling pathway are related to eating disorder ( Figure 3).…”
Section: Identifying Representative Genes In the Adipocytokine Signalmentioning
confidence: 99%